PENGARUH EKSTRAK BROTOWALI (Tinospora crispa L.) TERHADAP RASIO SEX DAN PERTUMBUHAN MENCIT (Mus musculusL. SWISS WEBSTER) - Susanti, Lusi - (Pendidikan Biologi, 2014)
Brotowali is a traditional medicine plants have potential be contraception. The active substance at Brotowali is Alkaloid, have antiproliferatif in reproduction cell. This aimed is reasearch to find out the Effects of Brotowali extract (Tinospora crispa L.) in sex ratio and the growth of mice (Mus musculus L. Swiss Webster). This research isexperiment research used completelly randomizeddesign with 4 treatments and 6 replication. The treatments are Brotowali extract, as P1 (given extract solvent/CMC 5%), a dose of 5x mg/bb (P2), 6x mg/bb (P3) and 7x mg/bb (P4). This research was conducted in January 2014 in Zoology Laboratory of Biology FMIPA UNP. The Parameter observed dead fetus, lived fetus, male female sex ratio and the weight growth of mice new baby born. The data is analisys by ANOVA and Varians Ranking One Tail Kruskall Wallis then through by Wilcoxonâs Rank Sum Test. The resultshows that Brotowali extract effect to sex ratio of mice, and decreases of live fetus percentage, increases of dead fetus percentage and not significant the weight of mice. It can concluded that brotowali extract effect to sex ratio, without effect to the growth of mice.